2017
DOI: 10.1249/mss.0000000000001384
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sex on Heart Rate Variability at High Altitude

Abstract: Increasing HA leads to a reduction in HRV. Significant differences between men and women emerge at HA. HRV was not predictive of AMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 26 publications
4
40
1
Order By: Relevance
“…Boos et al (2016) recently investigated various cardiopulmonary responses to acute normobaric hypoxia (simulated 4800 m) and did not detect any sex differences. In contrast, the same authors report differences between sexes with regard to HR variability indices when acutely exposed to various altitudes, which, however, were not predictive for AMS development (Boos et al, 2017). In line with our findings, similar resting (and exercising) cardiorespiratory responses to acute hypoxia have been reported in young and older subjects of a large cohort (Lhuissier et al, 2012;Richalet et al, 2012;Richalet and Lhuissier 2015).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Boos et al (2016) recently investigated various cardiopulmonary responses to acute normobaric hypoxia (simulated 4800 m) and did not detect any sex differences. In contrast, the same authors report differences between sexes with regard to HR variability indices when acutely exposed to various altitudes, which, however, were not predictive for AMS development (Boos et al, 2017). In line with our findings, similar resting (and exercising) cardiorespiratory responses to acute hypoxia have been reported in young and older subjects of a large cohort (Lhuissier et al, 2012;Richalet et al, 2012;Richalet and Lhuissier 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Reduced BG values at high altitude are hard to interpret since they do not represent fasting values but may at least partly be explained by enhanced carbohydrate oxidation during the short-term high-altitude exposure (Goto et al, 2015). The lack of differences between sexes, at least regarding cardiovascular and ventilatory responses to acute exposure to high altitude or hypoxia, is consistent with earlier and recent studies as well (Muza et al, 2001;Boos et al, 2016Boos et al, , 2017. For instance, Muza et al (2001) demonstrated a nearly identical time course of ventilatory acclimatization in female lowlanders who rapidly ascended to 4300 m compared with reports of male lowlanders.…”
Section: Discussionsupporting
confidence: 78%
“…The influence of HA on the changes in cardiac inter-beat intervals (IBI), known as heart rate variability (HRV), has been an area of significant recent research interest (Huang et al, 2010; Karinen et al, 2012; Boos et al, 2016a, 2017b; Mellor et al, 2017). This attention relates, in part, to the fact many of the factors that are known to affect HRV (e.g., fatigue, stress, insomnia, hypoxia, and cold) are predominant at HA (West, 2006; Kemp et al, 2012; Kiviniemi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that HA exposure is associated with significant changes in HRV compared with sea-level/low altitude (Huang et al, 2010; Karinen et al, 2012; Boos et al, 2016a, 2017b; Mellor et al, 2017). However, the majority of the published data relate to short-term HRV recordings (1–5 min) obtained conducted in hypoxic chambers during ‘simulated’ rather than genuine terrestrial HA (Vigo et al, 2010; Prabhakaran and Tripathi, 2011; Mairer et al, 2013; Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation